STUDI ANALISIS TENTANG PEMIKIRAN PENDIDIKAN ISLAM NUKMAN SULAIMAN - Helma Fitri; Saiful Akhyar Lubis; Achyar Zein (UIN Sumatera Utara Medan, 2019)
This research based on interest of researcher about Thought of Nukman Sulaiman and His contribution in Islamic Education. Nukman Sulaiman is a theologian which is not many people did research about his thougt in education field, mean while Nukman Sulaiman is a very productive theologian in deliver paper of research dan active in scientific activity especially in Islamic education in Al Wasliyah in North Sumatera. Based on that reason this research formulate two problem formulation: 1. What is specification Islamic education purpose of Nukman Sulaiman? 2. Describe and analyze Nukman Sulaiman Thought about Islamic education purpose? As for purpose of this research is: Describe and analyze education purpose of Nukman Sulaiman. As for this research is quantitative in design library research and using character study approach and data analyze technique that used triangulation technique. Result of research analyze study thought of Islamic education Nukman Sulaiman is: Specification education purpose formulated by Nukman Sulaiman is to forming believer and devoted human, knowledgeable, virtous, smart and clever in reaching happiness of the world and the hereafter. Those purpose is suitable with purpose of national education dan meaning content from education purpose in integration education purpose between world science and esthacology.